Activation of Multiple Phoneme Associates of Graphemes in Visual Word Recognition - Lange, Marielle (Brain & Language, 2002)
One general issue in the domain of visual word recognition is to delineate the nature of readers'' knowledge of the print-sound mapping. A more specific question is to determine whether multiple grapheme–phoneme associations are available and activated during the phonological transcoding of a letter string. Evidence for the activation of irregular associations during print-to-sound transcoding, independently from lexical influences, was assessed in a letter detection task by examining performance on target-absent pseudowords. We contrasted two types of pseudowords that could be considered homophone with a real word by application of either grapheme–phoneme correspondence rules or of multiple phonemic activation. Performance on both types of homophones was compared to nonhomophone control pseudowords, strictly equivalent in terms of orthographic similarity to the base words. The finding of a homophony disadvantage for the homophones by multiple activation was interpreted as evidence for multiple phonemic activation in the print-to-sound conversion system.